Knowledge Hiding in Emergency Ambulance Healthcare Settings: Its Mediating Role in the Relationship between Organizational Support and Affective Commitment and Organizational Citizenship Behaviours - Lucia Ratiu; Sabina R. Trif; Nicoleta Meslec (MDPI AG, 2021)
Knowledge hiding-an intentional attempt to withhold or conceal knowledge from others-has been reported by recent studies to be a negative phenomenon in the workplace. Considering the importance of knowledge for organizational performance, this study intends to advance understanding by investigating the mediating role of knowledge hiding on the relationship between perceived organizational support and affective commitment as predictors and organizational citizenship behaviors and turnover intentions as outcomes. Using a cross-sectional design, the study was conducted in emergency ambulance healthcare settings on 305 medical or paramedical professionals. As indicated by structural equation modeling results, perceived organizational support and affective commitment positively predicted organizational citizenship behaviors but negatively predicted turnover intentions. Also, knowledge hiding was negatively associated with perceived organizational support, affective commitment, and organizational citizenship behaviors and positively with turnover intentions. Moreover, knowledge hiding mediated the relationship between perceived organizational support and affective commitment as predictors and organizational citizenship behaviors, respectively turnover intentions, as dependent variables.